A slow-growth model for fast-growing broilers: effects on breast meat quality and myopathy incidence - Gungoren, G.; Simsek, U. G.; Gungoren, A.; Yilmaz, R.; Otlu, O. (Taylor & Francis Ltd, 2026)
1. This study evaluated the effects of a biologically calibrated pair-feeding model on breast meat yield, quality traits, biochemical markers and pectoral myopathy (PM) incidence in different broiler genotypes. 2. Fast-growing Ross 308 and Cobb 500 breeds were pair-fed according to the voluntary intake of a slow-growing strain (Hubbard Red JA) to moderate growth trajectory. A total of 300 broilers were allocated to ad libitum or pair-fed groups. Birds were slaughtered at comparable target live weights. Breast muscle yield, proximate composition, pH, colour (L*, a*, b*), water-holding capacity (WHC), cooking loss (CL), serum creatine kinase (CK), lactate dehydrogenase (LDH), calcium (Ca2+), malondialdehyde (MDA) and histopathological lesion scores were evaluated. 3. Pair-feeding significantly reduced breast muscle weight in Ross 308 and Cobb 500 (p < 0.001). In Ross birds, pair-feeding lowered CK (p < 0.001), LDH (p < 0.001) and Ca2+ (p = 0.046) concentrations and significantly reduced myodegeneration, fibrosis, infiltration and total myopathy scores (p < 0.001). Cobb birds had reduced CK (p = 0.014) and LDH (p < 0.001) but showed limited histopathological improvement (p > 0.05). 4. Pair-feeding increased lightness (L*) and decreased redness (a*) values at early post-mortem measurements (p < 0.001), while effects on ultimate pH (p = 0.003 in Ross) and WHC (p < 0.001 in Ross) were modest and genotype-dependent. Cooking losses were significantly decreased in both Ross (p < 0.001) and Hubbard strains (p < 0.001). 5. These findings suggested that pair-feeding based on slow-growing intake patterns can partially mitigate PM incidence and improve selected meat quality traits in fast-growing broilers, particularly Ross 308. However, genotype-specific responses indicated that growth-moderating strategies should be tailored to genetic background.
Keywords: Broiler breeds; pair-feeding; pectoral myopathies; breast meat quality; feed restriction; Ross 308; Cobb 500; Hubbard